Quaternary deformation along the Meeman‐Shelby Fault near Memphis, Tennessee, imaged by high‐resolution marine and land seismic reflection profiles. Issue 3 (30th May 2013) - Hao, Yanjun; Magnani, Maria Beatrice; McIntosh, Kirk; Waldron, Brian; Guo, Lei
Abstract [1] A series of high‐resolution seismic reflection surveys was carried out in 2008, 2010, and 2011, providing a total of five new seismic profiles constraining the location and character of the Meeman‐Shelby Fault (MSF), about 9 km west of Memphis, Tennessee, in the Central U.S. The MSF is the best documented fault closest to Memphis yet discovered and shows a recurrent fault history. The fault, as imaged by the reflection profiles, is ~45 km long, strikes N25°E, and dips west‐northwest ~83°, exhibiting an up‐to‐the‐west sense of motion with a possible right‐lateral strike‐slip component. The data show that on average, the MSF offsets the Paleozoic unit ~77 m and folds the top of the Cretaceous unit and the Paleocene‐Eocene Wilcox Group ~44 and ~25 m, respectively. One seismic profile acquired along the Mississippi River images the bottom of the Quaternary alluvium warped up ~28 m, indicating recent activity of the MSF. Calculated vertical slip rates of the MSF during the deposition of the Upper Cretaceous, Paleocene, Eocene, and Quaternary sediments are 0.0022, 0.0010, 0.0004, and 0.2154 mm/yr, respectively, suggesting an increase in fault activity during the Quaternary. Consistent with the present stress field and the deformation of the New Madrid seismic zone fault system, we interpret the MSF as a P shear fault in the context of a left‐stepping, right‐lateral constraining strike‐slip fault system under a nearly east‐west oriented compressional stress field. Source scaling estimates indicate that the MSF is capable of generating a M6.9 earthquake if rupturing in one event.